Improve Students' Critical Thinking Skills About Energy and Its Use Through the Society Technology Science Learning Model - Siregar, Torang; Rangkuti, Ahmad Nizar; Suparni, Suparni; Nasution, Enni Sumanti; Harahap, Sinar Devi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
This research aims to increase students' interest in science subjects regarding Energy and its use in utilizing natural resources, describing the use of concrete props in the science learning process to increase activeness and creativity in learningencourage students to think critically in Energy material and its use in utilizing natural resources and their solutions. From the results of this research, it is hoped that it can provide benefits in improving student learning outcomes optimally, increasing students' interest and motivation in quality science lessons which are considered difficult, increasing understanding of concepts, because students learn directly about themincreasing teacher creativity in carrying out the learning process, helping teachers develop their teaching abilities professionally, growing and increasing self-confidence, advancing school institutions as seen from increasing teacher professionalism in the learning processimproving and enhancing the learning process and outcomes of transfer students, creating a conducive school education situation. In the process of learning science for class IV on the subject of economic activities in Indonesia, the results of observations from colleagues, suggestions from supervisors, the author needs to carry out improvements to the learning of Natural Sciences (Science) subjects on the subject of energy sources and their use in the classroom IV (four). There were 20 students (71.43%) out of 28 students who had not met the KKM/score less than 75.in implementing learning improvements in Natural Sciences (Science) subjects starting from cycle I, it has shown an increase in students'mastery of the material with 15 students achieving completeness out of 28 students with an average score of 72.86.